A política de pagamento por serviços ambientais como mecanismo de promoção e efetivação a um meio ambiente ecologicamente equilibrado: uma análise comparativa da lei federal nº 14.119/2021 e da lei estadual nº 18.427/2023 - Silva, Maria Rosana Rocha da (2024)
The prevailing antagonism between environmental protection and economic development constitutes one of the biggest problems to be resolved today. Therefore, the general objective of this work is to examine the National Policy for Payment for Environmental Services (PNPSA) as a link between environmental law and the economic legal order, revealing an environmental support structure aligned with the active participation of civil society, in order to investigate how the legal system can make environmental protection actions more effective. As a possible parameter for resolving this problem, a comparative analysis will be made between Federal Law No. 14,119/2021 and State Law No. 18,427/2023. With this objective, initially, a legal assessment will be made regarding the relationship established between law and the economy; in which topics relating to liberalism and economic interventionism will be addressed; without neglecting the constitutional principles relating to the economic order; giving special emphasis to the study of Norberto Bobbio's Promotional Theory of Law, in order to relate it to the fundamental right to an ecologically balanced environment. The aim is, therefore, to reach the conclusion that the intersection between law and economic order constitutes an element that promotes more effective environmental protection both at the federal and state levels, especially with regard to the State of Ceará.